Twentieth Century Spectacle. Music and Power - Marija Ristivojević (University of Belgrade, 2016)
Review of the book by Miroslava Lukić Krstanović. Spektakli XX veka: Muzika i moć. [Twentieth Century Spectacle. Music and Power]. 2010. Beograd: Etnografski institut SANU. Posebna izdanja 72